Demonstration Gardens in the University of Florida Cooperative Extension Service - Sydney Park Brown; Kim Taylor; Emily Eubanks (EDIS)
Revised! ENH-865, a 21-page illustrated directory by Sydney Park Brown, Kim Taylor, and Emily Eubanks, lists by county the demonstration gardens of the UF Cooperative Extension Service. Published by the UF Department of Environmental Horticulture, October 2007.